Early outcomes in MDR-TB and XDR-TB patients treated with delamanid under compassionate use. Issue 1 (27th July 2017) - Hafkin, Jeffrey; Hittel, Norbert; Martin, Alexandra; Gupta, Rajesh
Multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) remain significant global health challenges, with an annual incidence of approximately 480 000 and 46 000 cases, respectively [1]. Treatment outcomes in MDR-TB patients remain poor overall (52% success) and outcomes in XDR-TB patients are even more dismal (28% success) [1–3]. To improve these outcomes, new drugs are needed [4]. Delamanid, a nitroimidazooxazole agent that has been included in the guidelines for MDR-TB treatment by the World Health Organization (WHO), has been shown to improve two-month sputum culture conversion (SCC) and long-term treatment outcomes, when added to an optimised background regimen (OBR) in MDR-TB patients [5–7]. As part of a global access initiative, Otsuka Pharmaceutical Co., Ltd. in coordination with the European Respiratory Society (ERS)/WHO TB Consilium, and Médecins Sans Frontières/Partners in Health (MSF-PIH) established its first Compassionate Use (CU) programme in February 2014 to provide patients with very limited treatment options access to delamanid. We present here early safety and efficacy outcomes of patients enrolled in this effort. Early data from the CU programme show delamanid may be effective in MDR/XDR-TB with few treatment options http://ow.ly/tA6Y30cs2Yg